Effect of nano phase change materials on the cooling process of a triangular lithium battery pack. (July 2022) - Alqaed, Saeed; Almehmadi, Fahad Awjah; Mustafa, Jawed; Husain, Shahid; Cheraghian, Goshtasp
Abstract: This paper simulates a nano-PCM (NPCM) in a circular enclosure where an inverted triangle is placed in its middle. Inside the barrier is a li-ion battery pack (LIIBP) with a triangular arrangement. The desired NPCM is made by adding graphene nanoparticles (NPs) in PCM, CaCl2 .6H2 O. There are 12 blades (BLs) on the middle LIIBP. The unsteady simulations are performed in two modes of melting and freezing of NPCM using the finite element method. The charging and discharging process of the PCM is investigated while the LIIBP temperature is kept constant. Simulations are done by employing COMSOL Multiphysics software. The percentages of molten material, average Nu, TAve, and local temperature are studied by altering the blade length (LBL) during the melting and freezing of NPCM. The results demonstrate that under the identical circumstances, the melting time of NPCM is longer than the freezing period. An enhancement in the LBL intensifies the TAve of the NPCM in the melting process and reduces the TAve in the freezing process. Enhancing the LBL increases the amount of NPCM at constant times from the beginning of the melting and freezing processes. The complete melting time of NPCM in a longer BL is less than that in bladeless mode. The same behavior is observed for freezing time. Graphical abstract: Unlabelled Image Highlights: Simulating a nano-PCM in a lithium battery pack Effect of blade on the cooling process of a triangular lithium battery pack Cooling lithium-ion batteries by a passive method Use of graphene in the process of the PCMs for the circular enclosure